Trust Understanding in Cloud and It’s Services (International Journal of Engineering and Computer Science, 2014)
The Cloud can be considered as a platform or infrastructure that is responsible for  execution of services and applications in a reliable and elastic fashion with predefined quality parameters to provide more Availability, agility, adaptability, reliability etc. In Brief, 'cloud' is an elastic execution environment of resources involving multiple stakeholders and providing a metered service at multiple granularities for a specified level of quality (of service). There are various services provided by cloud service providers to their users such as Saas, Pass, Iaas, these services are available to the cloud users depend upon some trust agreement across the globe. Trust is the another factor which is one of the most challenging issue in the cloud computing area for which various models has been proposed in last few years. The objective of this paper is to impart a clear idea about various services provided by cloud, there comparative approach and the role of various trust mechanism in cloud